International legal regulation of the protection of children’s rights in armed conflicts: Declarations and reality - HREKUL-KOVALYK, Tetiana; TSYMBALIUK, Andrii; HORDASH, Andriy (Revista Jurídica Portucalense, 2024)
The relevance of the research is driven by the fact that children belong to the most vulnerable groups of the population during armed conflicts and often become victims of violence, cruel treatment, forced displacement, and deprivation of access to education, medical care, and other basic needs. These risks have significantly increased with the full-scale invasion of the Russian Federation into the territory of Ukraine. Considering this, the aim of this scientific research is the necessity to investigate the effectiveness of international legal acts as a means of protecting children’s rights in times of war. The methods used in the study include statistical analysis, legal hermeneutics, analysis, and induction. The main results consist of clarifying the lawful and guaranteed rights of the child, which are provided for by both international conventions and Ukrainian legislation. The regulatory framework is detailed, including an analysis of the Convention on the Rights of the Child, the Geneva Conventions, the Law of Ukraine “On the Protection of Childhood,” and so on. It is indicated that the norms of the analysed acts prove to be insufficiently effective in the conditions of modern armed conflicts, which is confirmed by statistics. For example, approximately 2,000 children have been recorded as affected in the territory of Ukraine, and according to the United Nations, 468 million children live in regions of heightened danger. Children in such regions may suffer from various forms of violence, recruitment into armed formations, become victims of abductions, and deportations. Attention is focused on the necessity of reforming the modern child protection system in times of war by updating international conventions and creating specialized institutions aimed at providing medical and psychological rehabilitation for children who are victims of military aggression. The results of the scientific research can be used by lawyers and sociologists as a basis for improving Ukrainian legislation regarding the protection of children, as well as for international approaches to formulating security measures for minors in times of war.